INTERPRETASI AGAMA DALAM RUTINITAS KESEHARIAN MASYARAKAT KOTA LANGSA - Yogi Febriandi (Department of Anthropology, 2018)
This article examines the interpretation of religious teachings in the daily routine of the people of Langsa, Aceh. Langsa is an area that applies Islamic law like Aceh in general. The Langsa religious culture is not different from other Aceh regions. It's just that Langsa, more displays the cosmopolitan region with various ethnicities and religions that have mingled together. In sociology, Langsa displays the criteria for a bureaucratic and semi-industrial middle city. in such conditions, it is interesting to see the interpretation of religion in the Langsa community to see the influence of bureaucratic and semi-industrial modern life. The study was conducted with a phenomenological method with additional data in the form of interviews with 2 informants. The results of the study indicate that the interpretation of religion in Langsa takes various forms. This is because of the difference in the experience of community interaction with social conditions which gives rise to a variety of interpretations. In general, the interpretation of religion in Langsa still shows the condition of the formality where religion as a demand in humans interacts with God, not with humans.